Level of knowledge about death certificates in recently graduated physicians - Soto-Cáceres, Víctor Alberto (2021)
Objetive: specify the level of knowledge about the correct completion of death certificates in doctors who start the rural urban marginal health service (SERUMS). The study: descriptive cross-sectional design. Population: attending the SERUMS induction course: 86 recent graduates. Instrument: questionnaire with questions based on the "Technical Guide for the correct completion of death certificates 2018" Ministry of Health. Findings: 23% of the total have a terrible level, 41% bad, 34% fair and 2% good; the majority do not know how to specify the basic cause of death and 98% do not consider the accident circumstance as the basic cause and 85% do not know about SINADEF. Conclusions: The level of knowledge about the correct completion of the death certificate is very low with great ignorance to locate the basic cause of death.